The Quality Management of Vocational Midwifery Education: Literature Review: Manajemen Mutu Pendidikan Kebidanan Vokasi: Literature Review - Wati, Ratna; Nopriyanto, Dwi; Fadhilah, Desi; Azainil; Laili Khomariyah (Manajemen Pendidikan Program Doktor, 2025)
Improving the quality of midwifery education is essential to ensure competent graduates capable of contributing to the reduction of maternal and neonatal morbidity and mortality. This study aims to review the challenges and strategies for strengthening the quality of vocational midwifery education through a narrative review of 14 national and international articles. Using a thematic analysis approach, the literature was synthesized to identify key issues affecting educational quality. The findings indicate several major challenges, including variations in lecturer and clinical preceptor competencies, limited laboratory and clinical learning facilities, theory–practice gaps, inconsistent implementation of internal quality assurance, and difficulties in applying competency-based curricula. Strategies for improving quality include strengthening QA and PDSA cycles, implementing ISO 9001:2015, optimizing simulation-based learning, enhancing educator capacity, and integrating interprofessional collaboration competencies. This review highlights the need for systemic and continuous efforts to improve the quality of midwifery education in Poltekkes.